2017
DOI: 10.1021/acs.inorgchem.6b02870
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation, Vibrational and Electronic Properties of K2Ce(PO4)2: A Combined Experimental and Theoretical Study

Abstract: Herein we report the high-temperature crystal chemistry of KCe(PO) as observed from a joint in situ variable-temperature X-ray diffraction (XRD) and Raman spectroscopy as well as ab initio density functional theory (DFT) calculations. These studies revealed that the ambient-temperature monoclinic (P2/n) phase reversibly transforms to a tetragonal (I4/amd) structure at higher temperature. Also, from the experimental and theoretical calculations, a possible existence of an orthorhombic (Imma) structure with almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Since the monoclinic phase comes from the original lattice type of a distorted cubic system [67] it is supported the growth of this phase on the interface with the SrTiO 3 cubic phase. Several works [19,20,68] reported the phase transitions between different levels of symmetry (cubic, tetragonal and monoclinic), and emphasize that among the factors for the transition are the temperature increase in the interface that entails in entropy variation, serving as the driving force for the transition of phase. Goutenoire et al [69] evaluating the transition from monoclinic to cubic phase in the La 2 Mo 2 O 9 system, reported that the higher symmetry is obtained by oxygen diffusion in the crystalline lattice according to the temperature variation.…”
Section: High Resolution Transmission Electron Microscopy (Hr-tem)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the monoclinic phase comes from the original lattice type of a distorted cubic system [67] it is supported the growth of this phase on the interface with the SrTiO 3 cubic phase. Several works [19,20,68] reported the phase transitions between different levels of symmetry (cubic, tetragonal and monoclinic), and emphasize that among the factors for the transition are the temperature increase in the interface that entails in entropy variation, serving as the driving force for the transition of phase. Goutenoire et al [69] evaluating the transition from monoclinic to cubic phase in the La 2 Mo 2 O 9 system, reported that the higher symmetry is obtained by oxygen diffusion in the crystalline lattice according to the temperature variation.…”
Section: High Resolution Transmission Electron Microscopy (Hr-tem)mentioning
confidence: 99%
“…However, these works are related to single phase materials and not for heterojunctions with interface formed with different chemical compounds, phases and crystalline lattices tensions. It has been reported in several works that physical chemistry parameters deriving from growth surface between materials [18] and from synthesis procedure [19,20] can promote changes in crystalline phase stability, and hence changes on energy emission behavior. Different synthesis have been proposed in order to modulate the heterostructure properties, but, traditional methods are generally complex [10,14,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The calculations for the complex waste compounds studied here yield 0 K representative formation enthalpies such that they are metastable with respect to their simpler constituent oxides, lying above the 0 K thermodynamic convex hull. ,,, Thermal entropic contributions are important for these materials and can naturally influence the relative stability of crystal structures, affecting ranking of each candidate structure. ,, While including temperature-dependent contributions could potentially change our understanding of the relative stabilities, adding thermal contributions requires several phonon calculations per structure. , Although these calculations are possible for individual studies, , the length of time to carry out these calculations on a database scale would require significant computational resources that are not available. Even the use of approximate thermal corrections would require an extensive number of calculations for each candidate crystal structure and, as such, were not attempted. , We are currently evaluating approximate methods to add thermal contributions to our calculations such that we can obtain Gibbs energies for subsets of modeled compounds and thus predict possible reaction pathways for novel waste form materials. , …”
Section: Discussionmentioning
confidence: 99%
“…The calculations for the complex waste compounds studied here yield 0 K representative formation enthalpies such that they are metastable with respect to their simpler constituent oxides, lying above the 0 K thermodynamic convex hull. 5,33,48,65 Thermal entropic contributions are important for these materials and can naturally influence the relative stability of crystal structures, affecting ranking of each candidate structure. 32,33,36 While including temperaturedependent contributions could potentially change our understanding of the relative stabilities, adding thermal contributions requires several phonon calculations per structure.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation